The Endocannabinoid System in the Postimplantation Period: A Role during Decidualization and Placentation - B. M. Fonseca; G. Correia-da-Silva; M. Almada; M. A. Costa; N. A. Teixeira (International Journal of Endocrinology)
Although the detrimental effects of cannabis consumption during gestation are known for years, the vast majority of studies established a link between cannabis consumption and foetal development. The complex maternal-foetal interrelationships within the placental bed are essential for normal pregnancy, and decidua definitively contributes to the success of this process. Nevertheless, the molecular signalling network that coordinates strategies for successful decidualization and placentation are not well understood. The discovery of the endocannabinoid system highlighted new signalling mediators in various physiological processes, including reproduction. It is known that endocannabinoids present regulatory functions during blastocyst development, oviductal transport, and implantation. In addition, all the endocannabinoid machinery was found to be expressed in decidual and placental tissues. Additionally, endocannabinoid’s plasmatic levels were found to fluctuate during normal gestation and to induce decidual cell death and disturb normal placental development. Moreover, aberrant endocannabinoid signalling during the period of placental development has been associated with pregnancy disorders. It indicates the existence of a possible regulatory role for these molecules during decidualization and placentation processes, which are known to be particularly vulnerable. In this review, the influence of the endocannabinoid system in these critical processes is explored and discussed.